Terrorism : a critical introduction - Jackson, Richard, 1967- (Red Globe Press, 2011)
"Terrorism has a long history but the devastating attacks of 9/11 transformed what had been seen as a relatively minor security issue into one of major global significance. This incisive new text provides an accessible and balanced assessment of political terror and its study and in the process rethinks many assumptions"--